EFFECT OF FORTIFICATION OF FRESHWATER MUSSEL SHELL (Pilsbryoconcha exilis) FLOUR ON COOKIES TOWARDS CONSUMER ACCEPTANCE - Putri, Desrili Niatami; Hasan, Bustari; Iriani, Dian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study was aimed to determine the effect of fortification of freshwater mussel shell (Pilsbryoconchaexilis) flour on cookies towards consumer acceptance. The experimental method was used in this research with one factor of Completely Randomized Design (CRD), namely the addition of freshwater mussel shell flour on cookies production with 4 levels of concentration: 0% (CK-0), 0.5% (CK-0.5), 1% (CK-1), and 1.5% (CK-1.5). The parameter tested was consumer acceptance with 80 untrained panelists. The results showed that 1% (CK-1) treatment was the best treatment based on consumer acceptance with appearance 100%, color 98.75%, odor 100%, and flavor 100%.The characteristics for cookies produced were neat, the surface of cookies was flawless, brilliant and shiny yellow of color with a little bit brown color on the bottom. The odor of cookies was thought to originate from the mussel shell flour and the ingredients for cookies such as butter and vanilla which have a fragrant and not fishy odor and good taste and the mussel shell flour was not felt. However, based on the statistical analysis that the fortification of mussel shell flour on cookies production did not significantly different among treatment with 95% of confidence level. Keywords: Catfish Shell flour, freshwater mussel, Pilsbryoconcha exilis, cookies, consumer acceptance